2012
DOI: 10.1007/s12070-011-0430-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Perioperative Treatment with Calcium and with Calcium and Vitamin D in Prevention of Post Thyroidectomy Hypocalcemia

Abstract: Even though thyroid surgery is quite safe, mechanical damage, devascularization or inadvertent removal of the parathyroid glands are possible. Though postoperative mortality is extremely low, post thyroidectomy hypocalcemia is one of the most common and potentially life-threatening complication following thyroid surgery. The clinical manifestation varies from minimal twitching to life threatening tetany and can prolong the hospital stay. The purpose of this study is to evaluate the clinical usefulness of routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…). The reasons for exclusion of studies were a non‐randomized design, different intervention, and a preoperative intervention with no data on postoperative hypocalcaemia. Study characteristics are summarized in Table and Table S2 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…). The reasons for exclusion of studies were a non‐randomized design, different intervention, and a preoperative intervention with no data on postoperative hypocalcaemia. Study characteristics are summarized in Table and Table S2 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…According to several studies conducted by different authors, variation in urinary calcium concentration was not different when comparing thyroidectomized patients with those undergoing other procedures (Edafe, Mech, & Balasubramanian, 2019;Mazoni et al, 2022;Nemade, Rokade, Pathak, Tiwari, & Sonkhedkar, 2014;Ponce de León-Ballesteros et al, 2020). The authors found that calciuria decreased after all procedures, returning to preoperative values on the second day after surgery.…”
Section: Urinary Alterationmentioning
confidence: 97%
“…Otra variable utilizada para predecir y estratificar el riesgo de hipocalcemia es la medición seriada de niveles de calcio sérico. El nadir de hipocalcemia es a las 24-72 horas después de cirugía, aunque puede ocurrir hasta 15 días después, y se ve alterado por esquemas profilácticos de calcio/ calcitriol, estado acido-base, estado nutricional, niveles de magnesio, albumina y citrato, hemodilución, deficiencia de vitamina D prequirúrgica, liberación de calcitonina por manipulación tiroidea o síndrome de hueso hambriento 1,5,11,[18][19][20][21] . De esta manera, se considera que la variación del calcio sérico en las primeras horas de cirugía predice la evolución posterior de la siguiente forma: la presencia de una tendencia neutral o positiva predice normocalcemia con valor predictivo positivo del 86-100 % y la tendencia negativa se asocia con desarrollo posterior de hipocalcemia 18 .…”
Section: Introductionunclassified